THE ANALYSIS OF PUBLIC SERVICE QUALITY TO THE COMMUNITY IN THE WONOTIRTO SUB-DISTRICT OFFICE OF BLITAR REGENCY - Sulistyo Anjarwati (Universitas Islam Balitar, 2018)
Service to the community is the main goal of the government which is impossible to cause because the government must provide the best for the community, because it has made an agreement with the government, it is fitting for the government to find the best solution for problems related to needs. to prioritize the quality of community services for offices in Wonotirto sub-district. The research method used in this study is a quantitative method. The norm assessment is also conducted to see the high, medium or low of each dimension of service quality and after the data has been processed with the help of SPSS 16.00 computer for windows. The results of this study answer 75 respondents to the quality of community service in Wonotirto Sub-District Blitar Regency is good (seen in the average respondent responding well to each notification); The average score of the largest average percentage is 61.9% -80%.